Analisis Berfikir Kritis Siswa yang Bergaya Kognitif Reflektif dan Implusif pada Pembelajaran Biologi melalui Model Think Talk Write (TTW) dengan Media Limbah Pengolahan Hasil Laut - Isniar Putri Malyani; Imas Cintamulya (Universitas Sebelas Maret, 2017)
The development of the 2013 curriculum in the direction of national education is based more on the strengthening of reasoning, rather than rote. One of the goals of national education is developing the ability of critical thinking in the learning process. In addition, other aspects that need to be considered by the teacher is the cognitive style of students. Because each student has a different cognitive style. Because it is necessary to do research on critical thinking analysis of students who cognitive style of impulsive impractical using Think Talk Write model with the waste media processing of seafood. The subjects were 22 eighth grade students of MTs M 03 Sedayulawas consisting of 8 students with reflective cognitive style and 8 cultivated impulsive style sides. Data collection techniques are Matching Familiar Figures Test (MFFT) tests developed by Warli (2010) to determine civic side style and critical thinking skills that refer to the Ennis (1985) indicators. Furthermore, critical thinking data of reflective and impulsive cognitive style will be analyzed using Mann Whitney test. The results showed that there is a difference between the ability of the cognitive-style perspective style higher value than the critical thinking skills of cognitive-impulsive students. So, it can be concluded that the critical thinking skills of cognitive reflective-style students is better than the critical thinking skills of cognitive-impulsive students in biology lessons using Think Talk Write learning model with waste processing media of seafood.